Experimental Determination of <1010> / Ψ Tilt Grain Boundary Energies in Ice - Druetta, Esteban (2013)
Ice grain boundary energies γgb relative to the free surface energy γs were determined by studying the topographic details revealed by plastic replicas of the ice grain boundary groove-free surface with a Laser Confocal 3D Microscope. The samples analyzed were high purity ice bicrystals, with ‹101– 0›/Ψ tilt grain boundaries, annealed at –18 o C. Values obtained of γgb/γs were analyzed using coincidence site lattice (CSL) theory. Significant correspondence was found between the γgb/γs values and the planar density of coincident sites on the interface plane. The results show that γgb/γs depends on the GB inclination and may be up to one order of magnitude different.